(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Agricultural stakeholders are concerned about the anticipated crop production before the harvest. Many countries throughout the world employ computational technique’s for predicting yield ahead of harvest to assess a country’s food security and issue warnings about impending food shortages. This is a common method that aids strategy planners and decision-makers, particularly in rural economies. Crop statistical models have been used to track crop development and forecast production. The only inputs available at the field level will yield a prediction for a narrow region; remote sensing observations cover a broad area. They may be repeated at regular intervals, allowing for large-scale crop modelling. Crop yield prediction study necessitates a variety of production parameters and algorithms. Some algorithms are used to determine the optimum feature subset for improved prediction, while others are used to determine prediction. The proposed Correlation based Sequential Forward Feature Selection (CSFFS) is compared with the existing feature selection approaches. The classification with proposed feature selection attains effective accuracy in crop prediction.